Etching of fission tracks in monazite: An experimental study - Jones, S.; Gleadow, A.; Kohn, B.; Reddy, Steven (WILEY, 2019)
This study reports a range of etching and annealing experiments to establish the optimum conditions for the etching of fission tracks in monazite. The previously reported concentrated (12 M) HCl etchant at 90°C was found to cause grain loss from epoxy mounts and high degrees of grain corrosion, as did much longer etching times at lower temperatures. Using implanted 252 Cf semi-tracks, a series of experiments were performed on internal prismatic faces of monazite-(Ce) crystals from the Palaeozoic Harcourt Granodiorite (Victoria, Australia) using an alternative 6 M HCl etchant, also at 90°C. Step-etch results show optimal etching at 60–90 min. Further, an isothermal annealing experiment illustrated that the degree of annealing that can be expected during etching at 90°C under laboratory time scales is negligible. The etching rate between grains is not uniform, with a correlation demonstrated between over-etched grains and high U and Th concentrations.